Properties Of Epoxy/Silica Thin Film Composite For Electronic Application. - M, Mariatti; Foo, Y.L.; A, Azizan; Sim, L.C. (2010)
In line with the miniaturization trends of the product designs in electronic industry, conventional packaging technology has been replaced.